The importance of distance delimitation references in the teaching of hurdle technique - Palacios, L. S.; Martinez, C. C. (New Studies in Athletics, 2016)
As young athletes are exposed to hurdle training it is important that they acquire a complete knowledge of the technique through an appropriate and comprehensive pedagogical approach. In their coaching, the authors found that despite various fun approaches to teaching the event, fear and instinct lead young athletes, in most situations, to approach the hurdle too closely before take-off. To address this problem, they propose the use of visual limiting references for the impulse or take-off point to help ensure a correctly judged and aggressive take-off, which leads to a quick clearance of the hurdle, minimises the loss of horizontal velocity during the flight and facilitates the efficient continuation of the race. This study describes the test of their hypothesis through a six-week training programme with two groups of young athletes. In their conclusions they find that the use of visual limiting references significantly improves performance and is therefore a valuable tool that facilitates learning of the technique required for the correct hurdle clearance in young athletes.